Imbalances between the European Union and China - Ari Kokko (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2015)
China's impressive development since the introduction of market-oriented reforms in the late 1970s has had a considerable impact on the world economy. After a first decade and a half of cautious experiments with liberalization, markets, and internationalization, Chinese reforms accelerated in the early 1990s and the Chinese economy started growing at a rate that has not been matched by any other country. The GDP growth rate has averaged nearly 10 percent per year since that time. China has become the world's largest exporter and one of the largest importers, with a huge domestic market driven both by export-oriented industry and nearly 1.4 billion increasingly affluent domestic consumers. It is one of the main destinations for foreign direct investment (FDI) and has also become an important outward investor. The emergence of this new economic superpower has created both opportunities and challenges for other countries. The purpose of this paper is to focus on some of the challenges and to discuss three imbalances that put pressure on the relationship between the EU and China. These concern the large deficit in Europe's trade with China, the unequal conditions for European investment in China and Chinese investment in Europe, and the EU's inability to agree on a common China policy.
hdl:10398/9146
Keywords: 330; Internationale Wirtschaftsbeziehungen; Auslandsinvestition; Außenwirtschaftspolitik; China; EU-Staaten